ANALISA MINAT MAHASISWA DALAM BERWIRAUSAHA - Erny Rachmawati; Tiara Pandansari (Kompartemen : Jurnal Ilmiah Akuntansi, 2016)
The issue that will be examined is that of student interest in entrepreneurship. This is measured from how big the strengths and weaknesses of the students in self-employment, so do the results of the data collection will be a materials analysis to facilitate interpretation. The results of an entrepreneur is one who has the power of encouragement in order to obtain something objective, in this research turns out to be most highly represented on the grain question to my Q9 'person responsible', and Q10 with questions ' I love working hard. 'When compared with previous research results, research results and present problems interest or the spirit of entrepreneurship still shows the conclusions vary or differ. It still has the opportunity to research a type. Whereas a continuation of the research ' interest ' is the research on interest in self-employment.